1992
DOI: 10.1099/0022-1317-73-10-2517
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Grapevine Fanleaf Virus Satellite RNA Transcripts in Chenopodium quinoa Protoplasts

Abstract: A set of full-length cDNA clones of the satellite RNA of grapevine fanleaf nepovirus isolate Fl3 (GFLV-F13) was constructed with a variable number of additional, non-viral nucleotides at the 5' and 3' ends. The biological activity of the RNAs transcribed from these constructs was tested in Chenopodium quinoa protoplasts using a helper virus. When inoculated with arabis mosaic virus S (ArMV-S) RNA as helper, transcripts with 33 non-viral nucleotides at the 5' end (tr45p4) did not replicate, whereas transcripts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…until 96 h in infected protoplasts. In similar experiments Hans et al (1992) demonstrated that viral RNAs are actively replicated to reach a maximum 96 h p.i. and that CP, detectable 24 h p.i., also accumulates.…”
Section: P41fllmentioning
confidence: 81%
See 2 more Smart Citations
“…until 96 h in infected protoplasts. In similar experiments Hans et al (1992) demonstrated that viral RNAs are actively replicated to reach a maximum 96 h p.i. and that CP, detectable 24 h p.i., also accumulates.…”
Section: P41fllmentioning
confidence: 81%
“…2 a, lanes 5-10), based upon their size and by comparison with the in vitro maturation products, probably correspond to the P66 and P94 maturation intermediates and polyprotein P2 respectively. Further identification of polyprotein P2 and P94, both of which are precursors of CP, was attempted using antibodies raised against intact virions (Hans et al, 1992, and data not shown). Neither P94 nor P2 could be detected, due apparently to the reduced concentration of these precursor forms in the protoplast extracts and to the poor sensitivity of the antivirion antiserum on denatured CP.…”
Section: P41fllmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 2 x 105 C. quinoa protoplasts prepared according to Hans et al (1992) were inoculated by electroporation in 0.5 ml 0-6 M-mannitol, 0.1 mM-CaCI2, pH 5-6 with capped transcripts obtained from 10 gg cDNA1 and/or 7.5 gg cDNA2. After 30 rain incubation on ice the protoplasts were washed and incubated at 22 °C in the presence of 0-3 mg/ml carbenicillin for 72 h. Total RNA from protoplasts was extracted as described by Hans et aL (1992).…”
Section: P3725mentioning
confidence: 99%
“…Total RNAs were then extracted from 2 g of upper non-inoculated leaves by the method of Jackson & Larkins (1976) and further purified by precipitation in 2 ~u-LiCI , The RNAs were separated by electrophoresis under denaturing conditions on agarose-formaldehyde gels and transferred to Hybond N membranes (Amersham). The viral RNAs were detected with labelled riboprobes as described by Hans et al (1992).…”
Section: P3725mentioning
confidence: 99%